Człowiek kultury druku w świecie przyszłości – kino science fiction wobec teorii środków przekazu Marshalla McLuhana - Kowalczyk, Marcin (Przestrzenie Teorii, 2019)
Kowalczyk Marcin, Człowiek kultury druku w świecie przyszłości – kino science fiction wobec teorii środków przekazu Marshalla McLuhana [Man of Print Culture in the Future World – Science Fiction Cinema and Marshall McLuhan’s Media Theory]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 239–255. ISSN 1644-6763. DOI 10.14746/pt.2019.32.12. This article shows the way of presenting the characters who represent print culture in science fiction cinema. All the printed artifacts, like literature, books and letters, are defined according to Marshall McLuhan’s media theory. The analysis is based mostly on the movie Her (dir. Spike Jonze, 2013) and discusses how SF movies adapt and transform the twentieth-century predictions concerning print as a medium. This approach allows us to avoid a simple interpretation of the problem, where books or print become merely a sign of civilization that has passed. Furthermore, McLuhan’s theory helps effectively reveal the complex motivations of the characters who are shaped by a specific medium.